2022
DOI: 10.1016/j.cognition.2021.104940
|View full text |Cite
|
Sign up to set email alerts
|

Children are more exploratory and learn more than adults in an approach-avoid task

Abstract: Intuitively, children appear to be more exploratory than adults, and this exploration seems to help children learn, but there have been few clear tests of this idea. We test whether exploration and learning change across development using a task that presents a "learning trap." In this task, exploitation-maximizing immediate reward and avoiding costs-may lead the learner to draw incorrect conclusions, while exploration may lead to better learning but be more costly. In Studies 1, 2, and 3 we find that preschoo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 69 publications
8
50
0
1
Order By: Relevance
“…Adults seem more motivated than children to maximize performance in these tasks. This interpretation is in line with results from reinforcement learning tasks where children demonstrate biases toward exploratory strategies, whereas adults consistently use strategies that maximize reward (Blanco & Sloutsky, 2019, 2020Gopnik, 2020;Liquin & Gopnik, 2022).…”
Section: Adults Generally Learn Better Than Childrensupporting
confidence: 84%
“…Adults seem more motivated than children to maximize performance in these tasks. This interpretation is in line with results from reinforcement learning tasks where children demonstrate biases toward exploratory strategies, whereas adults consistently use strategies that maximize reward (Blanco & Sloutsky, 2019, 2020Gopnik, 2020;Liquin & Gopnik, 2022).…”
Section: Adults Generally Learn Better Than Childrensupporting
confidence: 84%
“…Finally, our study focused on young adults and 68.5% were college students. This could be important as explore-exploit behavior is known to change with age in childhood ( 49 ) and adolescence ( 48 ), which are key periods for the development of mental health. Students could also differ from non-students in the same age range (although we did not find evidence for differences between students and non-students on the measures included here).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with sex were included because sex differences have been observed in both cognitive reflection measures (37)(38)(39)(40)(41)(42) and symptoms of emotional disorders (43)(44)(45)(46)(47). Age was included due to previous work showing changes in exploratory behavior across childhood and adolescence (48,49). Models included exploration measures as predictors of depression/anxiety symptoms, cognitive reflection measures as predictors of exploration measures, and cognitive reflection measures as predictors of depression/anxiety symptoms.…”
Section: General Reflectiveness Measuresmentioning
confidence: 99%
“…Learning is akin to exploring, whereas acquiring may present a trade-off between exploration and exploitation because people choosing to acquire objects may balance between trying new options and sticking with familiar ones. So given the aforementioned developmental shift from explore to exploit (Gopnik, 2020 ; Liquin & Gopnik, 2022 ), we might have expected children to predominantly prefer having atypical items. Instead, we found that children and adults both preferred having familiar items.…”
Section: Discussionmentioning
confidence: 99%